Learning Multimodality through Genre-Based Multimodal Texts Analysis: Listening to Students’ Voices - Fuad Abdullah; Soni Tantan Tandiana; Yuyus Saputra (Vision: Journal for Language and Foreign Language Learning, 2020)
Recently, multimodality has attracted the attention of researchers, notably in the educational milieu. However, only a few studies reported on the way students perceived the use of Genre-Based Multimodal Texts Analysis (GBMTA) for teaching multimodality. After addressing the gap, this study focuses on students’ perceptions on the use of GBMTA in multimodality teaching in higher education. Sixty-nine students were involved in the study. Each of the students produced one journal through three meetings. The journals were then collected for document analysis and thematic analysis (Braun Clarke, 2006). The findings reveal that the students perceived GBMTA as facilitating them in the building of multimodal discourse analysis, challenges and solutions of comprehending multimodal teaching materials, planning better learning strategies in the future, engagement on multimodal learning issues, and multimodal text analysis practices. This study contributes to multimodality teaching or multimodal discourse analysis within genre-based learning.